2018
DOI: 10.1016/j.cmet.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Etomoxir Inhibits Macrophage Polarization by Disrupting CoA Homeostasis

Abstract: Long-chain fatty acid (LCFA) oxidation has been shown to play an important role in interleukin-4 (IL-4)-mediated macrophage polarization (M(IL-4)). However, many of these conclusions are based on the inhibition of carnitine palmitoyltransferase-1 with high concentrations of etomoxir that far exceed what is required to inhibit enzyme activity (EC < 3 μM). We employ genetic and pharmacologic models to demonstrate that LCFA oxidation is largely dispensable for IL-4-driven polarization. Unexpectedly, high concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
261
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(288 citation statements)
references
References 65 publications
24
261
2
1
Order By: Relevance
“…Moreover, careful examination of the effect of etomoxir on T cell metabolism has suggested that, at high concentrations, this compound has multiple off-target effects on mitochondrial metabolism and other cellular processes, which may vary depending on the cellular context and requirements for activation, influencing the differentiation of not only T cells, but also other immune subsets such as macrophages (143, 146). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, careful examination of the effect of etomoxir on T cell metabolism has suggested that, at high concentrations, this compound has multiple off-target effects on mitochondrial metabolism and other cellular processes, which may vary depending on the cellular context and requirements for activation, influencing the differentiation of not only T cells, but also other immune subsets such as macrophages (143, 146). …”
Section: Resultsmentioning
confidence: 99%
“…With a half-maximal inhibitory concentration in the nanomolar range (IC 50 = 10–700 nM), etomoxir is a potent inhibitor of CPT1 (140143). Nonetheless, there are important caveats to consider when using this compound.…”
Section: The Role Of Lc-fao In Cd8+ Tmem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…To highlight these issues, hematopoietic stem cells were thought to possess very little mitochondrial mass based on mitochondrial dye stains. 166 Furthermore, genetic ablation of CPT2, which carries long-chain fatty acids into the inner matrix of the mitochondria, was unable to recapitulate findings obtained on etomoxir treatment of cells, implying therefore an inconsistency between pharmacological and genetic data. 163 As another example of how drug manipulations should be treated with caution, we performed pharmacological experiments with plasma cell subsets and etomoxir, an inhibitor of fatty acid oxidation, to define the carbon sources that drive basal respiration.…”
Section: Methods To Assess Plasma Cell Metabolismmentioning
confidence: 99%